HISTORY OF THE HUNGARIAN ECONOMIC TRAINING - Cseh-Papp, Imola; Varga, Erika (Journal of process management and new technologies, 2017)
Economics is a relatively young branch of science. It became an independent subject at the end of the 18th century. Everything that existed before can only be regarded as antecedents. Taking the educational-political situation of the economic training into consideration it was pushed to the periphery in the past centuries in the Carpathian Basin. Profound changes took place only with the Austro-Hungarian Compromise of 1867 when the state paid more attention to catching up the most disadvantaged regions, which resulted in giving a new impetus to industrial development. Our paper makes an attempt to summarize the history of the economic training in the Carpathian Basin. Without giving all the details it tries to take account of the events (of the fight for an independent university of economics) from the beginnings through the history of Collegium Scientiarum Politico Oeconomico Cameralium, the events of the University of Nagyszombat, the foundation of József (Joseph) Technical School and the history of József nádor (Palatine Joseph) University of Technology and Economic Sciences to the foundation of the first Marxist university and later the introduction of the Bologna system.